Weakening of rainfall intensity on wet soils over the wet Asian monsoon region using a high-resolution regional climate model - Takahashi, Hiroshi G.; Polcher, Jan (Progress in earth and planetary science, 2019)
This study estimated the sensitivity of rainfall characteristics (rainfall amount, rainfall frequency, rainfall intensity, and rainfall extremes based on 30-min intervals) to land-surface conditions over Southeast Asia, which has a wet land surface during the rainy season. To obtain the regional difference in sensitivity and simulate basic cloud-precipitation systems, we used a high-resolution regional climate model. To extract the systematic signals of sensitivity and exclude random errors, a series of six sensitivity experiments, which were driven by a reanalysis dataset and the observed sea surface temperature (SST), were conducted over the Indochina Peninsula. In our experiments, soil moisture was prescribed at 0.20, 0.25, 0.30, 0.35, 0.40, and 0.45 m 3 m −3 over the whole domain and during the whole calculation period. More experiments would allow us to divide the responses into systematic signals and random noise. The slope of a meteorological variable as a function of the six prescribed soil moisture values was defined as the sensitivity. It was found that the sensitivity of rainfall frequency to soil moisture was positive overall, whereas the sensitivity of rainfall intensity was negative overall, although evapotranspiration (sensible heat flux) increased (decreased) in a manner similar to the increase in soil moisture over the whole domain. The sensitivity of rainfall amount to an increase in soil moisture was dependent on the location. This implies that the response of rainfall characteristics to soil moisture is not simple, suggesting that changes in rainfall characteristics are not solely determined by evapotranspiration. In addition, the sensitivity of rainfall characteristics displayed remarkable regional characteristics. The characteristics described above were noticeable over the inland flat plains. We also discussed the mechanism in the response of rainfall characteristics to soil moisture. The coupling of an increase in water vapor in the planetary boundary layer and a decrease of sensible heat flux can explain the response. The increase in water vapor in the planetary boundary layer was associated with a reduction of the development of deep convections and an increase of boundary layer clouds.